Performance of catenary mooring system - Abd. Samad, Faisal Ikram (2009)
The number of deep water moored offshore vessels is growing rapidly, and hydrocarbon fields in water depths down to 3000 m are now seriously considered for floating production development. The exploration drilling or offshore floating production units with superior mooring capacity thus become a highly demand factor. Concerning on this booming drilling activity has driven this research to be carried out to analyze the mooring system requirement as well as the behaviour of the floating structure when experiencing external forces such as wave and current forces. The purpose of this study is to investigate the technical as well as performance analysis of the catenary mooring system from the perspective of a Spar platform drilling unit. The main part comprises an analysis and discussion on the mooring configuration, material and weight, length of mooring line required to resist the environmental loads and movement of the platform. This study will utilized the finite element approach and the analysis will be carried out by using M-File programming from MATLAB software package. The endeavour of this paper is to develop theoretical methods for evaluation of Spar oil platform response with catenary mooring lines and to carry out performance analysis of the catenary mooring lines between static and dynamic mooring system. The performance of mooring system is determined as the ability of the system to establish superior station-keeping capabilities for the floating platform, so to ensure that horizontal excursions of the platform are not so large as to cause damage to the production risers or the sub-sea equipment and subsequently enabling production and export risers to remain connected for the life of the field.